2008
DOI: 10.3324/haematol.12165
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of treatment outcome in acute myeloid leukemia by measurement of WT1 transcript levels in peripheral blood samples collected after chemotherapy

Abstract: The Wilms' tumor gene WT1 is a reliable marker for minimal residual disease assessment in acute leukemia patients. The study was designed to demonstrate the potential use of WT1 to establish quality of remission in acute leukemia patients for early identification of patients at high risk of relapse. A prospective study based on a quantitative Real-Time PCR (TaqMan) assay in 562 peripheral blood samples collected from 82 acute leukemia patients at diagnosis and during follow-up was established. The evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 22 publications
6
82
0
1
Order By: Relevance
“…WT1 expression has already been shown to be a helpful marker in patients with AML after chemotherapy, 19,[21][22][23] after autologous 24 and after conventional allogeneic HCT. [25][26][27] In this analysis, the ability of different markers to predict relapse following allogeneic HCT with RIC was analyzed both alone and in combination.…”
Section: Introductionmentioning
confidence: 99%
“…WT1 expression has already been shown to be a helpful marker in patients with AML after chemotherapy, 19,[21][22][23] after autologous 24 and after conventional allogeneic HCT. [25][26][27] In this analysis, the ability of different markers to predict relapse following allogeneic HCT with RIC was analyzed both alone and in combination.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 Increased levels of WT1 detected by PCR have been shown to be a prognostically useful marker of MRD. [52][53][54] It has also been shown to be a predictor of relapse in AML patients who have undergone hematopoietic SCT. 55,56 A recent study showed that the combined use of MFC and WT1 monitoring could distinguish between patients with high and low risk of relapse after hematopoietic SCT.…”
Section: Future Directionsmentioning
confidence: 99%
“…This means these patients can be treated with intensified chemotherapy protocols. 2 The major obstacle in MRD detection by RT-PCR or quantitative PCR (RQ-PCR) is represented by the limited percentage of AML patients presenting with detectable genetic aberrations. 3 The use of alternative markers for MRD detection suitable in the vast majority of AML patients, and in particular to test WT1 expression as a universal marker of leukemic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Survival is highest for children with M3 sub-type. 2 After treatment of AML in children, either is in remission or in minimal residual disease (MRD). In general, children with detectable MRD during or after induction chemotherapy are more likely to develop relapse and may require more intense treatment 2 Evaluation of MRD in children with AML after induction therapy is important to predict prognosis and may improve selection of the type and intensity of post-remission treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation